Pretesting Mathematical Concepts with the Mobile Phone: Implications for Curriculum Design - Kizito, Rita Ndagire (International Review of Research in Open and Distributed Learning, 2012)
One of the neglected elements when teaching at a distance is establishing what learners already know at the beginning of the course or module. Unlike the face-to-face environment, in distance learning there is no opportunity for administering diagnostic activities just before the onset of instruction. This means that both the weak and more advanced students receive the same level of support since there is no mechanism for differentiating their learning needs. This paper describes the characteristics of a diagnostic test aimed at determining student understanding of the basic calculus concepts of the derivative and the integral, using the mobile phone as the method of delivery. As a proof-of-concept exercise, 10 questions designed to test concept attributes and procedural knowledge involving the two basic calculus concepts were given to a sample of 30 students at the beginning of the course. The implications for curriculum design were then analysed in terms of the didactical functionalities and the communication strategy that could be developed with reference to the mobile phone.